Nursing Care for Mr. S, Diagnosed with Pulmonary Tuberculosis (TB) in the Emergency Department (ED) of Gunung Jati Hospital in Cirebon City - Nadia Sindia Devi; Indah Mamay Maftuhah; Uswatun Khasanah; Neneng Rimawati Nurokhman; Endah Sari Purbaningsih (Al Makki Publisher, 2024)
Tuberculosis or TB is a disease caused by infection of the Mycobacterium tuberculosis bacteria in the lungs. This condition is sometimes referred to as pulmonary TB. Tuberculosis bacteria that invade the lungs cause respiratory problems, such as chronic cough and shortness of breath. TB patients usually also experience other symptoms, such as night sweats and fever. This study aims to provide an overview of the implementation of Nursing Care in patients with a medical diagnosis of Pulmonary Tuberculosis (TB) in the emergency room of Gunung Jati Hospital, Cirebon City. The method used is a case study approach. The subject in this case study was one patient diagnosed with Pulmonary Tuberculosis (TB) in the emergency room. The results showed nursing care management in patients diagnosed with Pulmonary Tuberculosis (TB). The nursing problem is Ineffective Airway Cleansing, which is carried out by interventions, namely effective cough techniques; interventions are carried out when the patient has difficulty removing sputum, the results obtained at the time of assessment, the patient complains of shortness of breath, coughing and difficulty removing sputum. Before performing effective cough techniques, respiration was 28x/minute, and after performing effective cough techniques, respiration decreased to 25x/minute. This study implies non-pharmacological techniques, such as effective coughing techniques, can be essential in managing patients with pulmonary tuberculosis alongside pharmacological therapy. This study provides a valuable contribution to improving the understanding and practice of nursing care in Tuberculosis cases in the hospital environment, especially in the emergency room of Gunung Jati Hospital, Cirebon City.